Unravelling the potential of prussian blue analogues in oxygen electrocatalysis: A perspective on surface reconstruction - Priya Jain; Pravin Popinand Ingole (Chemical Physics Impact)
Prussian blue analogues (PBAs) hold promises as catalysts for electrochemical energy conversion, especially in the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). Their high surface area and porosity combined with a tunable electronic structure featuring abundant metallic centers, make them attractive alternatives to traditional noble metal-based catalysts. Amongst these fascinating properties, the capacity for surface reconstruction to form active layers is one of the most sought-after characteristics of PBAs for enhanced activity. Recent advancements in operando and in situ techniques have further highlighted PBAs' capability for surface reconstruction during the electrocatalysis, particularly in alkaline solutions. State-of-the-art strategies for enhancing activity and stability of PBA-based catalysts, such as metal doping, tuning metal centers, introducing coordination sphere vacancies (VFeCN), and utilizing carbon supports, are closely linked to their ability towards surface reconstruction. However, key aspects warrant further exploration to achieve high electrocatalytic activity, including identifying initiators and pathways for surface reconstruction, establishing structure-property-activity correlations, and strategically manipulating in-situ catalyst surface reconstruction. This perspective focuses on understanding the transformation of PBA-based pre-catalysts to surface active layers on catalysts via surface reconstruction. A recent progress in PBA-catalysts towards advancing the electrochemical energy systems is highlighted. This perspective will guide the new entrants in the field to understand the process of surface transformation for establishing structure-property-activity relationships and thus to develop highly efficient PBA-based electrocatalysts.